Mortality salience increases language style matching and well-being. Issue 4 (3rd July 2016) - Cox, Cathy R.; Kersten, Mike
Abstract: The present research examined whether people imitate the language style of others (i.e., the use of function words) as a form of liking when mortality concerns are salient. In Study 1, participants answered questions about death or public speaking and then engaged in an instant messaging conversation with a confederate. In Study 2, participant pairs verbally discussed a news article about increasing homicide rates or the rise in academic pressure. Next, everyone completed measures of self-esteem, life satisfaction, and relationship need satisfaction. The results revealed that, in comparison to the control conditions, participants exhibited greater language style matching (LSM) following reminders of death (Studies 1 & 2). Further, mediational analyses showed that higher LSM after mortality salience was associated with better psychological and social well-being (Study 2). Although the threat of death has been shown to make people more hostile and disparaging toward dissimilar others, the present work suggests that individuals, even strangers, may feel closer through language coordination following thoughts of mortality.